Video-based lecture engagement in a flipped classroom environment - Gutiérrez-González, Raquel; Zamarron, Alvaro; Royuela, Ana (BMC medical education, 2024)
to analyze which factors are associated with students' engagement and participation in video-based lectures in a flipped classroom environment. A single-center experience with video-based lectures in undergraduate medical education is described. The activity was applied to the subject of Neurosurgery during two consecutive courses (2021/22 and 2022/23). The videos were available prior to face-to-face classes through the online application Edpuzzle. Information was obtained from the own platform at the end of each course. Multivariable linear regression analyses were performed to assess the association between different variables and the percentage of video viewing, the early dropout rate, and the percentage of audience retention. A total of 109 students registered in Edpuzzle (87.2% of all enrolled students). Fifty-one videos were uploaded each course to cover 11 topics. Mean video viewing rate was 41%. Those videos linked to the earliest classroom lessons showed more percentage of viewing and audience retention than those programmed at the end of the course. With mandatory classroom assistance and homework assignments, the seminar videos were viewed more but retained less audience. Shorter videos were associated with higher viewing and audience adhesion, but the presence of questions embedded throughout the clip did not significantly engage students. No significant difference was observed regarding lesson topics. It is essential to emphasize the importance of designing strategies to initially engage learners since more than half of our students never connected to the clips. Decreasing engagement was associated with the end of the course and video length. Seminar videos were viewed more but retained less audience. Active learning activities such as quizzes embedded throughout the clips did not significantly engage learners.